Measuring the impact of innovation on firm value: a new approach - Kornelius Kraft; Dirk Czarnitzki (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
Most of the existing empirical literature on the relationship of firm value and knowledge capital is based on the stock market valuation of companies. However, the assets of many firms are not publicly traded, and hence the calculation of market value is limited to a subsample of firms. We suggest to use a credit rating score instead and present an empirical analysis. It turns out that innovative firms, i.e. those with a reasonable knowledge stock, have a better credit rating and thus, as we propose, a higher value. However, too much of innovative activi-ties is seen as risky and the firm value decreases.
Keywords: C25; O31; O33; 330; Firm Value; Credit Rating; Innovation; Intellectual Property Discrete Regression Models; Innovation; Unternehmenswert; Kreditwürdigkeit; Schätzung; Deutschland